#TITLE_ALTERNATIVE# - HAMZAH
Slim hole drilling is a drilling that uses of the last casing / liner with a small diameter is size < 5 inch while the standard hole size of the casing / liner last used is > 5 inch and < 9.625 inch. Using slim hole drilling on exploration will save up to 3-4 times the cost (depending on the depth of drilling) so as to reduce the high risk exploration. However, the main disadvantage of slim hole drilling can not be used for production well. Therefore, in this study, we will calculate the pressure loss of the slim hole well by using Hagedorn-Brown and Homogeneous correlation. Thus, if the exploration of the slim hole well is successful, the data obtained from the slim hole wells can be used to calculate the discharge rate of standard hole well. Finally, a feasibility study of development can be determined and can also maximize the development of geothermal fields.